2000
DOI: 10.1111/j.1750-3639.2000.tb00243.x
|View full text |Cite
|
Sign up to set email alerts
|

Resuscitative Hypothermia Protects the Neonatal Rat Brain from Hypoxic‐Ischemic Injury

Abstract: The effect of 24h of hypothermic recovery on moderate hypoxic-ischemic brain damage in P7-rats was investigated for 42d after the insult, using magnetic resonance and histopathology. Occlusion of right common carotid artery and 90min exposure to 8% O2 at 37°C body temperature produced cytotoxic edema of 51(±11)% brain volume (BV) and depression of brain energy metabolism (PCr/Pi) from 1.43(±0.21) to 0.14(±0.11). During recovery, the body temperature was reduced to 30°C for 24h in 36 animals, but was kept at 37… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
25
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(27 citation statements)
references
References 47 publications
2
25
0
Order By: Relevance
“…Some of these reports have described a reduction by 42%-65% of the injured area when using hypothermia as neuroprotective strategy (30,31), a proportion very similar to that obtained with WIN. In addition, WIN reduced the shrinkage of the ipsilateral hemisphere observed after HI.…”
mentioning
confidence: 90%
“…Some of these reports have described a reduction by 42%-65% of the injured area when using hypothermia as neuroprotective strategy (30,31), a proportion very similar to that obtained with WIN. In addition, WIN reduced the shrinkage of the ipsilateral hemisphere observed after HI.…”
mentioning
confidence: 90%
“…However, in neonates with severe HIE, little neuroprotection could be achieved using current HT protocols in which whole-body or head cooling is performed for 48 to 72 h by maintaining the core temperature within a range of 33.5 to 34.5°C (2)(3)(4)(5). In animal studies, the efficacy of postischemic HT was also limited in the subgroup with severe ischemic injury (6,7). To treat severe HIE by HT, a recent review suggested a "deeper" and "more prolonged" cooling (8).…”
mentioning
confidence: 99%
“…10 In an animal study, hypothermia was also demonstrated to have protective effects in mild but not in severe hypoxia-ischemia. 11 Therefore, it is also useful to identify a noninvasive method to detect and monitor the evolution of HI-induced WM damage for treatment selection and to determine the effectiveness of treatment.…”
mentioning
confidence: 99%